2022
DOI: 10.1039/d1ta08256f
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Fe–N4 sites by introducing Bi–O bonds in a Fe–N–C system for promoting the oxygen reduction reaction

Abstract: Elemental Bi is effective in optimizing the electrocatalytic activity of perovskite oxides and noble metals, but has never been used to adjust the oxygen reduction activity of Fe/N-C catalysts. Here,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Bi element can effectively optimize the activity of peroxides and noble metals, but it is quite uncommon for it to increase the oxygen reduction activity of SACs catalysts. Jin et al 226 successfully synthesized a Fe/N-C catalyst with Bi-O forms (Fe/Bi-RNC) by using rod-like C 3 N 4 templates (Fig. 21a).…”
Section: Transition Metals and Transition Metalsmentioning
confidence: 99%
“…Bi element can effectively optimize the activity of peroxides and noble metals, but it is quite uncommon for it to increase the oxygen reduction activity of SACs catalysts. Jin et al 226 successfully synthesized a Fe/N-C catalyst with Bi-O forms (Fe/Bi-RNC) by using rod-like C 3 N 4 templates (Fig. 21a).…”
Section: Transition Metals and Transition Metalsmentioning
confidence: 99%
“…12,13 Fe-N-C catalysts derived from Fe partial substituted zeoliticimidazolate-framework-8 (ZIF-8) precursors show great promise in terms of abundant accessible active sites, satisfactory electronic conductivity and encouraging catalytic activity. [14][15][16][17] Unfortunately, isolated iron atoms are likely to migrate and aggregate during long-term catalytic reactions due to their high surface energy, resulting in degradation of catalytic activity. 18,19 Additionally, Choi et al 20 and Singh et al 21 found that the activity of Fe-N-C electrocatalysts would decrease dramatically when the FeN x active moieties are exposed to the by-product H 2 O 2 due to undesirable Fenton reactions.…”
Section: Introductionmentioning
confidence: 99%
“…1−3 Among them, the Zn−air battery is considered as one of the most prospective technologies for energy storage owing to the high energy density, considerable safety, and environmental friendliness. 4,5 However, the sluggish cathodic oxygen reduction reaction (ORR) involving a multielectron transfer process is one of the main obstacles to the development of Zn−air batteries. 6−9 Although noble-metal-based electrocatalysts, especially platinum (Pt-based catalysts), are state-of-the-art ORR catalysts, their large-scale commercialization is significantly blocked by the drawback of high cost and poor durability.…”
Section: Introductionmentioning
confidence: 99%
“…The exhaustion of traditional energy forces us to explore new energy conversion and storage techniques such as metal–air batteries and fuel cells with low carbon emission, meeting the increasing energy demand of social development. Among them, the Zn–air battery is considered as one of the most prospective technologies for energy storage owing to the high energy density, considerable safety, and environmental friendliness. , However, the sluggish cathodic oxygen reduction reaction (ORR) involving a multielectron transfer process is one of the main obstacles to the development of Zn–air batteries. Although noble-metal-based electrocatalysts, especially platinum (Pt-based catalysts), are state-of-the-art ORR catalysts, their large-scale commercialization is significantly blocked by the drawback of high cost and poor durability. So far, more durable and cost-effective non-noble-metal catalysts are identified as substitutes to Pt-based catalysts for ORR.…”
Section: Introductionmentioning
confidence: 99%